Stages of Settlement of International Civil Law Disputes: Tahapan Penyelesaian Sengketa Hukum Perdata Internasional - Adyaksa, Bryan Rois Putra; Niravita, Aprila (Annual Review of Legal Studies, 2024)
This research analyzes the stages of settlement of international civil law disputes in the case of Chin Hsiang Electricity & Machinery Co. Pte. Ltd. vs. P.T. Loka Rahayu Plywood Industries. The objective is to evaluate the settlement stages and their legal implications based on the theory of International Private Law (IPL). The research method used is qualitative with a conceptual, case, and comparative approach. Data was collected through literature and documentation studies. The results of the study show that the application of Indonesian Civil Law by the Jambi District Court judge was appropriate, but not transparent regarding the application of IPL. This raises doubts about the application of IPL principles and rules. The conclusion is that transparency in the application of IPL and the role of IPL decisions in the development of national and international law are very important.